Intermittent Central Suppression Suffered After a Rough Landing on a Bicycle. - Hussey, Eric S. (Optometry & Visual Performance, 2017)
Background: Seth, a 16-year-old male student-athlete, suffered a concussion during trail riding in 2014 when his bike came apart during a jump. The patient's occupational therapist referred him for a vision examination and therapy following vestibular therapy. Unresolved post-concussion symptoms included headaches, problems seeing the ball in sports, and reading problems reminiscent of "dyslexia.". Case Report: The initial specific examination of Seth's binocularity 4 months post-concussion showed intermittent central suppression (ICS). Since all symptoms began post-trauma, it is more likely than not that the suppression was a result of the head injury. Vision therapy concentrated on eliminating the ICS, including using rapid alternation with liquid crystals. Therapy was in-office, started slowly in order to respect his post-concussion symptoms, and also included standard eye movement and vergence therapies. Thirty-seven visits eliminated the suppression, confirmed at a progress evaluation 6 months post-therapy. Conclusion: Following therapy, the patient's symptoms were resolved, and he was able to return to riding his bike.